Faszyzm i sport w dziejach Włoch .......... 143 - Landoni, Enrico (Riflessioni intorno alla storia politica d’Italia = Refleksje wokół historii politycznej Włoch, 2025)
FASCISM AND SPORT IN ITALIAN HISTORYThis paper focuses on the distinctive features of fascist sports policy, retracing the various stages of the regimentation of the Italian sport movement and dwelling on the role played in this context by the National Olympic Committee.